(untitled) (Research, Society and Development, 2020)
Vegetable oils have a high oxidative rate that influences rheological properties and mainly increases acidity. However, licuri oil (Syagrus Coronata) has a high amount of saturated fatty acids and good oxidation stability. Therefore, this article aims to analyze the physical and chemical properties of oil extracted from licuri considered unsuitable for human consumption, in natura and transesterified. For this, laboratory research was carried. The specific mass test was performed using the pycnometer method. The viscosity and shear stress in a rheometer, while thermal conductivity was done in a probe-type thermal analyzer. The acidity index was performed using the acid / base titration method. The transesterification was by the basic route. The results of the oil in natura were compatible with other oils found in the literature. Transesterification influenced mainly acidity and rheological profile. It is concluded that the results were favorable and that the licuri oil can be used in different sectors of the industry with potential for use as base oil for biolubricants.